Green synthesis of imine-based covalent organic frameworks in water - Martín-Illán, Jesús Á; Rodríguez-San-Miguel, David; Franco, Carlos; Imaz, Inhar; Maspoch, Daniel; Puigmartí-Luis, Josep; Zamora, Félix (Chemical communications (Cambridge, England), 2020)
Dynamic covalent bonds have been advantageously used to direct the synthesis of crystalline porous covalent organic frameworks (COFs). Unlike the standard synthetic protocols that involve harsh conditions, this work provides a high-yield "one-pot" green synthesis of imine-based COFs in water. Additionally, this aqueous synthesis can be performed under microwave conditions, considerably reducing the reaction time.